2015
DOI: 10.2147/opth.s81976
|View full text |Cite
|
Sign up to set email alerts
|

Autologous platelet concentrate in surgery for macular detachment associated with congenital optic disc pit

Abstract: PurposeTo evaluate the anatomical and functional results obtained with pars plana vitrectomy (PPV) plus autologous platelet concentrate (APC) as a treatment for macular detachment associated with optic disc pit (ODP).MethodsWe performed a prospective interventional study of 19 eyes of 19 consecutive patients with posterior macular detachment due to ODP. All patients underwent PPV, posterior hyaloid peeling, fluid–air exchange, injection of 0.05 mL of APC over the ODP and 15% perfluoropropane (C3F8) endotampona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Also, of the patients with attached macula, 80% required more than 180 days for reattachment to occur. This is in keeping with previous studies that showed that improvement of vision is related to restoration of the normal retinal morphology [10-14, 19, 21, 22, 25-31]. This becomes progressively more evident 6–12 months postoperatively, as submacular fluid is slow to resolve (Table 3).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Also, of the patients with attached macula, 80% required more than 180 days for reattachment to occur. This is in keeping with previous studies that showed that improvement of vision is related to restoration of the normal retinal morphology [10-14, 19, 21, 22, 25-31]. This becomes progressively more evident 6–12 months postoperatively, as submacular fluid is slow to resolve (Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…Improvement of vision was achieved in 89% of our cases, with a mean visual gain of almost 3 lines on the Snellen chart at the end of the follow-up time, and 67% had a final BCVA of 0.5 or better. This compares favourably with other functional results [10-14, 19, 22, 25-31]. Similar functional outcomes have been reported by D’Souza et al [16] and Nawrocki et al [17] using the same surgical procedure.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, they could be used as a powerful therapeutic tool to trigger and enhance the healing process. Encouraging results were already achieved by the use of different platelet by-products in dental and maxillofacial surgery [5], in orthopedics [6,7], and in ophthalmology [8,9]. Clinical trials, demonstrating beneficial effects for the treatment of degenerative cartilage diseases, were conducted with platelet-rich plasma (PRP) [10] and also with autologous platelet lysate (PL) [11].…”
Section: Introductionmentioning
confidence: 99%